Investigation on clogging characteristics of permeable asphalt mixtures. (20th December 2020) - Meng, Anxin; Xing, Chao; Tan, Yiqiu; Xiao, Shenqing; Li, Jilu; Li, Guannan
Highlights: Explicit the particle distribution of pavement surface sediment. Clarify the clogging process of permeable asphalt mixture. Explore the void variation of permeable asphalt mixture in the clogging process. Analyze the influence parameters of clogging characteristics of asphalt mixture. Abstract: Characterizing the clogging process of permeable asphalt mixtures helps clarify the permeability of permeable pavements. This study aimed to determine the clogging characteristics of permeable asphalt mixtures. By analyzing the particle size of pavement surface sediment, the size of clogging particle was determined in the range from 0.15 to 2.36 mm. Five types of permeable asphalt mixtures were synthesized, and the clogging characteristics test was performed with the independently developed multidirectional permeability test instrument. The variation of the permeability in the clogging process was explored. Subsequently, the internal void of permeable asphalt mixtures was characterized by computerized tomography. As suggested from the results, the void evolution at different depths of specimen varied with the rise in the number of clogging particles. It was reported that the clogging process of permeable asphalt mixtures consisted of four stages, i.e., fast clogging, clogging recovery, gradual clogging and clogging acceleration. Under the clogging effect, the permeability of permeable asphalt mixtures could vary from non-Darcy to Darcy permeability, and the variation speed of the transverse permeability was faster than that of the vertical one. Lastly, the effects of water head height, the gradation type of permeable asphalt mixtures and clogging particles on the clogging characteristics were analyzed.